2017
DOI: 10.1158/1055-9965.epi-16-0863
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Calcium Intake and Lung Cancer Survival: A Pooled Analysis of 12 Cohort Studies

Abstract: Background Lung cancer is the leading cause of cancer death. Little is known about whether prediagnostic nutritional factors may affect survival. We examined the associations of prediagnostic calcium intake from foods and/or supplements with lung cancer survival. Methods The present analysis included 23,882 incident, primary lung cancer patients from 12 prospective cohort studies. Dietary calcium intake was assessed using food-frequency questionnaires at baseline in each cohort and standardized to caloric in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Moreover, another large cohort study reported a higher mortality benefit in patients ingesting 800–1,000 mg/d of supplemental calcium. 83 One meta-analysis failed to report similar associations 34 (Table 3). The effects of calcium on lung carcinogenesis remain controversial due to the complexity of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, another large cohort study reported a higher mortality benefit in patients ingesting 800–1,000 mg/d of supplemental calcium. 83 One meta-analysis failed to report similar associations 34 (Table 3). The effects of calcium on lung carcinogenesis remain controversial due to the complexity of the process.…”
Section: Resultsmentioning
confidence: 99%
“…We harmonized de-identified, individual participant data from 11 cohorts ( 16 , 17 ), including 7 US cohorts (National Institute of Health–American Association of Retired Persons Diet and Health Study; Health Professionals Follow-up Study; Nurses’ Health Study; Iowa Women’s Health Study; Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial; Southern Community Cohort Study; and VITamins And Lifestyle Study), 2 European cohorts (European Prospective Investigation into Cancer and Nutrition and Trøndelag Health Study), and 2 Asian cohorts (Shanghai Men’s Health Study and Shanghai Women’s Health Study). All studies were approved by the institutional review boards and ethics committees of the hosting institutes.…”
Section: Methodsmentioning
confidence: 99%
“…Potential confounders were selected a priori based on literature review and risk factors found in our study populations ( 16 , 17 ). Included were age at diagnosis (continuous), sex, race and ethnicity (Asian, Black, Other [Hispanic and Latino, American Indian, and other racial or ethnic group] and White), smoking status (never, former, current), smoking pack-years (continuous), education (less than high school, high school graduation, vocational education, college, university or higher), alcohol consumption (none, moderate drinking up to 1 and 2 drinks per day, heavy drinking >1 and >2 drinks per day for women and men, respectively; 1 drink = 14 grams of ethanol), history of diabetes (yes, no), body mass index (BMI; <18.5, 18.5-24.9, 25.0-29.9, and ≥30.0 kg/m 2 ), and hormone therapy in women (yes, no)—all of which were assessed at LTPA assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations